Research on Technogene/Anthropocene in Brazil - França Junior, Pedro; Korb, Carina Cristiane; Brannstrom, Christian (Quaternary and Environmental Geosciences, 2018)
This research aims to present a bibliographical review of the research related to the Technogene /Anthropocene in Brazil. The methodology consisted of bibliographic search in academic Google and in university library sites. The research was categorized according to environment and the geomorphological process: alluvial deposits and accelerated erosion; mining; dam siltation; urban and coastal environments. Of more than 200 publications pertinent to the theme, twenty-nine were selected to be synthesized. The research highlighted the heterogeneity of the knowledge that has already been produced on the Technogene / Anthropocene in Brazil. They corroborate the idea of humans as geological agents, but each study situates the geologic agency of humans in an environment with intrinsic geographic characteristics that provide the technogenic variations in the surface and sub-surface.